PATIENT SATISFACTION WITH THE QUALITY CARE PROVIDED BY NURSES AT THE BEDSIDE IN TERTIARY HEALTH INSTITUTE - JAVID , B; PERVEEN , T; NAZAR , K (Biological and Clinical Sciences Research Journal, 2023)
to compare the level of patient satisfaction based on their socio-demographic characteristics in tertiary care institutes. This study was conducted at Nishtar Hospital after getting ethical approval from ERC. It was conducted from January 05, 2023, to May 05, 2023, between patients 20-50 years of age who had been admitted to the hospital for at least five days, and both genders were included. Disoriented patients or those who refused to participate were excluded from this study. Data was collected using PSNCQQ, a 19-emit questionnaire with 5 responses of each item from poor to fair, good, very good, and excellent. Then comparison was made between the socio-demographic and PSNCQQ total score. SPSS version.21 was employed for this purpose. Descriptive statistics were depicted in frequencies (%ages), mean & SD. The level of significance was <0.05. This study revealed no significant difference between patient’s age, gender & marital status, and level of satisfaction with quality care provided by nurses (p>0.05). But the nature of the patient’s ward revealed a significant difference with p<0.05 and their satisfaction level with nursing care. It was concluded that the nature of the ward only affects the level of patient satisfaction by the nursing care they receive. And age, gender, and marital status do not affect their satisfaction level.